Postbiotics enhance the efficacy of derivative compound mouthwash against clinical Helicobacter pylori strains - Rawee Teanpaisan; Nuntiya Pahumunto; Nuntiya Pahumunto (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundA previous study indicated that poly L-lysine-glycerol monolaurate mouthwash reduced the virulence of Helicobacter pylori; however, these compounds are derivatives. Thus, this study aimed to compare the effects of postbiotics, postbiotic-glycerol monolaurate, and poly L-lysine-glycerol monolaurate mouthwashes against clinical H. pylori strains.MethodsPostbiotics, Lacticaseibacillus paracasei SD1, L. rhamnosus SD4, and L. rhamnosus SD11 were examined for anti-bacterial activity and synergistic effects. Subsequently, mouthwashes containing postbiotics, postbiotic-glycerol monolaurate, and poly L-Lysine-glycerol monolaurate were prepared and evaluated for their ability to reduce H. pylori adhesion to host cells, suppress inflammation induced by H. pylori, eradicate biofilm, decrease cagA expression, and assess epithelial cell viability. The stability of the mouthwashes was evaluated every 4 weeks up to 24 weeks for their efficacy against H. pylori growth, biofilm eradication, and epithelial cell viability.ResultsThe postbiotics, L. paracasei SD1 and L. rhamnosus SD11, demonstrated significant anti-H. pylori activity, with synergistic effects observed in combinations with derivative compounds. Postbiotic-glycerol monolaurate mouthwashes exhibited higher efficacy in reducing H. pylori adhesion to host cells (42.64-43.83%), suppressing pro-inflammatory cytokines, eradicating biofilm (82.62% at 24 h), and reducing cagA expression (112.60 fold) compared to others. Such mouthwashes also displayed low cytotoxicity (< 30% for 15 min) to all cells tested. The stability was observed up to 24 weeks.ConclusionThis in vitro study demonstrated that postbiotic-glycerol monolaurate mouthwash revealed the highest efficacy against H. pylori with low cytotoxicity to host cells. The stability lasted for 24 weeks.